2022
DOI: 10.3390/jcm11195626
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy and the Risk of Viral Infection: A Retrospective Population-Based Cohort Study

Abstract: Statins exert cholesterol-independent beneficial effects, including immunomodulatory effects. In this study, we attempted to investigate the association between statin therapy and the risk of viral infection. We conducted a retrospective cohort study using data from Taiwan’s National Health Insurance Research Database. We identified patients with hyperlipidemia and divided them into two cohorts: statin users and statin nonusers. A 1:1 propensity score matching was conducted between the two cohorts, and a Cox p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Might the targeting of metabolic pathways be useful clinically to promote antiviral immunity or limit autoimmunity via modulation of type I IFNs? Statins, which are targeting cholesterol metabolism significantly reduced risk of viral infection, including SARS‐CoV‐2 89,90 while data on mortality are unclear 91 . However, studies comparing the efficacy in humans are mostly retrospective, therefore comparing patients already using statins with cohorts without statin treatment 89,92–94 .…”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%
“…Might the targeting of metabolic pathways be useful clinically to promote antiviral immunity or limit autoimmunity via modulation of type I IFNs? Statins, which are targeting cholesterol metabolism significantly reduced risk of viral infection, including SARS‐CoV‐2 89,90 while data on mortality are unclear 91 . However, studies comparing the efficacy in humans are mostly retrospective, therefore comparing patients already using statins with cohorts without statin treatment 89,92–94 .…”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%
“…The study compared statin users ( n = 20,202) and non-statin users ( n = 20,202) from a population with hyperlipidemia. Statin treatment was associated with a significantly lower risk of viral infection in all age groups older than 18 years in both men and women, and this risk was reduced as the duration of treatment increased [ 137 ]. While this study only observed people with hyperlipidemia, and the mechanism by which statins might be associated with a lower risk of viral infections was not explored, the data obtained are certainly interesting when considering the potential of repurposing statins for EBOV infection.…”
Section: Ebola Virus: From a Therapeutic Point Of Viewmentioning
confidence: 99%